Egg Hatching and Larval Survival of Common Carp (Cyprinus carpio Linnaeus, 1758) Againts Exposure to Carbamate Insecticides with Different Concentrations - Ula, Linda Zahrotul; Latuconsina, Husain; Lisminingsih, Ratna Djuniwati (Agrikan Jurnal Agribisnis Perikanan, 2023)
The purpose of this study was to determine the value of Hours from the use of carbamate insecticides on hatchability of Common carp (Cyprinus carpio) eggs, to compare hatchability of carp (Cyprinus carpio) eggs exposed to carbamate insecticides at different concentration levels, to compare survival rates. goldfish exposed to carbamate insecticides at different concentration levels. This study used a completely randomized design (RAL) where there were 3 treatments and 1 control. In each treatment there were 3 replications. Data analysis used ANOVA and DNMRT tests. The results showed that the average percentage of goldfish egg hatchability was at a concentration of 0.4 ppm with 58% hatchability. While the percentage of survival is at a concentration of 0.4 ppm with hatchability of eggs is 56%. The results of acute toxicity test Hours of carp eggs are at a concentration of 0.8 ppm. The conclusion obtained is that the acute concentration of hours of carbamate pesticides with the active ingredient karbosulfan in Common carp eggs (Cyprinus carpio) is a concentration of 0.8 ppm. There are differences in egg hatchability and survival rate of carbamate (Cyprinus carpio) larvae on exposure to carbamate insecticides with different concentrations, and there is a tendency that the higher the concentration of carbamate insecticides used, the lower the hatchability of eggs and carbamate (Cyprinus carpio) larvae survival.